Comprehensive regulation and control method for surface insulation performance of solid-gas interface of ceramic material
By doping sintering aids to adjust the microstructure of the ceramic material, the problem of degradation of the insulation performance of the ceramic material along the surface in high-pressure gas insulation equipment is solved, and the comprehensive surface insulation performance optimization of the solid-gas interface of the ceramic material is achieved.
Patent Information
- Application Number
- CN202411939847.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
It is difficult for existing ceramic materials to maintain the insulation performance along the surface for a long time in high-pressure gas insulating equipment, especially under the action of temperature gradients and electric fields, and surface charge accumulation and reduction of the flashover voltage along the surface are prone to occur.
By doping different sintering aids, the microstructure of the ceramic material is adjusted to improve porosity, surface morphology, grain size and uniformity, thereby regulating the volume resistivity, temperature stability and surface charge accumulation characteristics of the ceramic material.
It significantly improves the surface insulation performance of solid gas interface of ceramic materials, enhances the temperature stability of volume resistivity, reduces surface charge accumulation, and increases the flashover voltage along the plane.
Smart Images

Figure CN119707508A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a method for comprehensively regulating the surface insulation performance of a ceramic material solid-gas interface. Background Art
[0002] At present, most high-voltage gas-insulated equipment uses polymer insulating materials such as polyethylene and composite insulating materials with epoxy resin as the matrix and doped with alumina particles as internal insulating materials. Compared with the insulation strength of SF6 gas, the surface insulation strength of epoxy resin composite insulators is lower, so the gas-solid interface between the insulator and SF6 is the weak point of insulation in the equipment. With the increase of voltage level and transmission capacity of DC transmission system, the electrical, thermal and mechanical working stresses inside the equipment gradually increase, and the surface insulation performance of epoxy resin composite insulation materials has not shown satisfactory results. First, under the temperature gradient, the surface field strength of epoxy resin composite insulation materials transfers to the low-voltage side, resulting in a significant increase in the field strength on the low-voltage side, which is very unfavorable to the surface insulation performance of the insulation structure, and this phenomenon will lead to a significant reduction in the surface flashover voltage. Secondly, the surface charge accumulation phenomenon of epoxy resin composite insulation materials in the DC electric field and the molecular decomposition and performance degradation of organic polymers under long-term thermal action are all important problems faced by epoxy resin composite insulation materials in high-voltage electrical insulation equipment. Therefore, there is an urgent need to explore new insulating materials that can effectively improve the long-term surface insulation performance of SF6 gas-insulated high-voltage DC electrical equipment.
[0003] Ceramic materials, as an insulating material with high thermal conductivity, high mechanical strength and high durability, have been widely used in power systems. However, traditional ceramic materials may be difficult to be compatible with strong electric field conditions and SF6 gas environment for a long time, and cannot be directly used in the design and manufacture of supporting insulators inside high-voltage gas-insulated equipment. In addition, the insulating support will be subjected to high-intensity electro-thermal stress for a long time, requiring the material to have a large volume resistivity and good temperature stability, and reduce the accumulation of surface charge to improve the surface flashover voltage of the ceramic material. Therefore, there is a need for a method to improve the comprehensive surface insulation performance of the solid-gas interface of ceramic materials by adjusting the microstructure of ceramics, so as to find a high-performance ceramic insulation material formulation system in combination with actual working conditions, and select a ceramic basic material system with high surface insulation strength and strong compatibility with SF6 gas according to the porosity, surface morphology, grain size, uniformity and number of grain boundaries of a wide variety of high-performance ceramic material formulation systems with different insulation properties, and conduct a comprehensive performance evaluation from the aspects of material volume resistivity and temperature stability, surface charge accumulation and surface flashover, and finally determine the ceramic material suitable for long-term insulation support function in SF6 environment. Summary of the invention
[0004] In view of the above problems, the present invention proposes a method for comprehensive control of the surface insulation performance of the solid-gas interface of ceramic materials. The ceramic materials are prepared by doping different sintering aids to adjust their microstructures, and the effects of the microstructure of the ceramic materials on the changes in volume resistivity with temperature, surface charge accumulation, and surface flashover voltage are observed and analyzed to control the comprehensive performance of the ceramic materials. Among them, in the internal insulation environment of high-voltage gas-insulated equipment, the internal insulation supports of the high-voltage gas-insulated equipment operate under complex electro-thermal stresses for a long time during operation. The heat generated by the guide rods causes the insulation supports to form a temperature gradient distribution, which is prone to surface flashover and performance degradation problems, significantly affecting the volume resistivity of the ceramic materials, thereby increasing their losses and charge injection. In addition, the temperature stability of the ceramic materials is poor under the temperature gradient, and electric field distortion and radial electric field enhancement are prone to surface charge accumulation at the solid-gas interface, thereby affecting the surface electric field distribution, causing the surface electric field of the insulation supports to be distorted, and thereby causing the surface flashover voltage to decrease. Therefore, the microstructure of the ceramic material is adjusted to comprehensively control the three material properties of its volume resistivity changes with temperature, surface charge accumulation, and surface flashover voltage.
[0005] After mixing the sintering aid with the ceramic material, the green body is obtained by ball milling, granulation, preforming and cold isostatic pressing, and then sintered at the optimal sintering temperature. The microstructure of the ceramic material doped with different elements is observed by scanning electron microscopy (SEM), and the relationship between the micromorphology of the ceramic and the insulation performance is studied. The porosity, surface morphology, grain size, distribution and uniformity of the ceramic material are improved by doping with sintering aids; the volume resistivity and temperature stability of the material can be adjusted by adjusting the carrier concentration and the height of the conduction barrier; the surface charge accumulation at the solid-gas interface of the ceramic material is reduced by adjusting the three factors of carrier concentration, grain uniformity and grain boundary structure, and the surface charge dissipation rate is increased. Combined with the surface charge accumulation characteristics of the ceramic material, the surface smoothness of the material is enhanced by adjusting the number of grain boundaries, grain size and uniformity of the material, so that the surface flashover voltage is increased.
[0006] A method for comprehensively regulating the surface insulation performance of a ceramic material solid-gas interface is characterized in that a sintering agent containing metal element ions or rare earth element ions is added to the ceramic material during sintering.
[0007] Preferably, the sintering agent is a combination of one or more.
[0008] Preferably, the metal element ion in the sintering agent is Mg 2+ or Ti 4+ .
[0009] Preferably, the rare earth element ion is Ba 2+ .
[0010] Preferably, Mg is added to the ceramic material at the same time. 2+ and Ti 4+ions, and the ratio between the two is 1:4-4:1.
[0011] Preferably, Mg is added to the ceramic material at the same time. 2+ and Ti 4+ and Ba 2+ ions, and Ba 2+ The doping mass fraction is 1%-4%.
[0012] Preferably, the mass fraction of the metal element ions or rare earth element ions added to the ceramic material during sintering is 2%-4%.
[0013] Preferably, Mg is added to the ceramic material during sintering. 2+ 、Ti 4+ and Ba 2+ , and the mass fraction ratio among the three is 3.2%:0.8%:4%.
[0014] Preferably, the sintering temperature is 1600°C to 1800°C.
[0015] Preferably, the ceramic material is alumina.
[0016] The beneficial effects of the present invention are as follows: In the present invention, the porosity, surface morphology, grain size, distribution and uniformity of the ceramic material are improved by doping a sintering aid to the microstructure of the ceramic material, thereby regulating the surface insulation performance of the solid-gas interface of the ceramic material. By adjusting the porosity, grain size and uniformity of the ceramic material and thereby changing the carrier concentration and the height of the conduction barrier, the volume resistivity of the material and its temperature stability can be adjusted. By adjusting the three factors of carrier concentration, grain uniformity and grain boundary structure, the surface charge accumulation at the solid-gas interface of the ceramic material is reduced, the surface charge dissipation rate is increased, and the surface smoothness of the material is enhanced, so that the flashover voltage along the surface is increased, thereby optimizing the surface insulation performance of the solid-gas interface of the ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the SEM image of the alumina grain size without any doping ions added;
[0018] Figure 2 is the SEM image of the alumina grain size after doping with 2% and 4% MgO respectively;
[0019] Figure 3 are doped with 2% and 4% TiO 2 SEM image of the alumina grain size after treatment;
[0020] Figure 4 are doped with 2% and 4% BaCO 3 SEM image of the alumina grain size after treatment;
[0021] Figure 5 It is doped with 2% of three different ions of Mg 2+ 、Ti 4+ , Ba 2+ The insulation properties of alumina ceramics, Figure 5 (a) is the volume resistivity variation with temperature, Figure 5 (b) is the surface charge accumulation characteristic, Figure 5 (c) is the surface flashover characteristic. DETAILED DESCRIPTION
[0022] The embodiments are described in detail below in conjunction with the accompanying drawings.
[0023] Most of the existing methods for comprehensive surface insulation performance of solid-gas interface of ceramic materials are for screening and evaluation of ceramic materials that can enhance a single characteristic, and no comprehensive regulation and research has been conducted on volume resistivity and its temperature stability, surface charge accumulation and surface flashover characteristics. Under the coupling of electric field and thermal field, ceramic materials with a single enhanced characteristic may encounter other challenges. In the internal insulation environment of high-voltage gas-insulated equipment, the internal insulation supports of high-voltage gas-insulated equipment operate under complex electro-thermal stress for a long time during operation. As the operation time increases, the internal insulation environment will become more and more complex. The heat generated during operation will cause uneven heating of the supporting insulators, resulting in temperature gradients in the supporting insulators, which are prone to surface flashover and performance degradation problems, significantly affecting the volume resistivity of ceramic materials. In addition, ceramic materials have poor temperature stability under temperature gradients, and are prone to surface charge accumulation at the solid-gas interface, causing the electric field on the surface of the insulating support to be distorted, which in turn leads to a decrease in surface flashover voltage. Therefore, how to reduce loss and charge injection and avoid electric field distortion under temperature gradient has become an urgent problem to be solved. Therefore, the present invention proposes a comprehensive control method for the surface insulation properties of the solid-gas interface of ceramic materials by doping sintering aids to adjust the microstructure of the material.
[0024] Ion doping has a great influence on the microstructure of ceramic materials. Ceramic materials have high activation energy, small grains without sintering aids, incomplete mass transfer, and sintering necks. By doping sintering aids to form a second phase or a liquid phase with ceramic materials, the fluidity during sintering is increased, the grains are refined and the uniformity of the structure is improved, the internal pores of the material are reduced, sintering is promoted, and the porosity, grain size, distribution, uniformity, and number of grain boundaries of ceramic materials are optimized.
[0025] The influence of microstructure on the variation of volume resistivity with temperature: The variation of volume resistivity of ceramic materials with temperature is determined by the ion conduction process in the material. The volume resistivity of the material can be adjusted by adjusting the carrier concentration and the height of the conduction barrier. Reducing the porosity of the material will lead to a decrease in the solid-gas interface inside the material and reduce surface defects, thereby reducing the carrier concentration and increasing the volume resistivity. Reducing the grain size of the material and enhancing the uniformity can reduce its grain boundary structure, reduce the occurrence of body migration, and reduce the deviation between the migration path and the electric field direction in crystal migration, reduce the conduction barrier, and enhance its temperature stability. Therefore, it is necessary to select ceramic materials with low porosity, appropriate grain size, and high uniformity to regulate its volume resistivity variation with temperature.
[0026] Effect of microstructure on surface charge accumulation characteristics: Surface charge accumulation of ceramic materials is affected by three factors: carrier concentration, grain uniformity, and grain boundary structure. Doping with sintering aids and functional ions such as metal ions and rare earth elements can reduce the porosity of ceramic materials, enhance the uniformity of grains, thereby reducing carrier concentration, making the electric field distribution uniform, inhibiting the process of charge migration from the inside of the ceramic material to the solid-gas interface, and reducing charge accumulation. At the same time, increasing the number of grain boundaries increases the charge dissipation rate, thereby reducing surface charge accumulation at the solid-gas interface. Therefore, it is necessary to select ceramic materials with low porosity, high grain uniformity, and a large number of grain boundaries to regulate their surface charge accumulation characteristics.
[0027] Effect of microstructure on surface flashover characteristics: The surface flashover voltage characteristics of ceramic materials are affected by the surface charge accumulation characteristics. Doping with suitable sintering aids can increase the number of grain boundaries in ceramic materials, provide more ways for charge dissipation, and reduce the surface charge accumulation at the solid-gas interface of the material. At the same time, the grain size is reduced, the grain uniformity is increased, and the material surface is smoother, thereby suppressing the electric field distortion on the material surface and increasing the surface flashover voltage. Therefore, it is necessary to select ceramic materials with high grain uniformity and a large number of grain boundaries to regulate their surface flashover characteristics.
[0028] The method for comprehensive control of the surface insulation properties of the solid-gas interface of ceramic materials described in the present invention prepares ceramic materials by doping different sintering aids to adjust their microstructures, and achieves control of the comprehensive properties of the ceramic materials such as volume resistivity changes with temperature, surface charge accumulation, and surface flashover voltage.
[0029] Preparation method of ceramic materials: Ceramic materials are mixed with different sintering aids in a certain proportion, and then ball-milled with anhydrous ethanol for 10 to 12 hours and dried at 80 to 100°C for 5 to 8 hours. After screening, the green body is obtained by granulation, preforming and cold isostatic pressing. The green body is placed in a tubular furnace at 600 to 800°C for debinding for 2 to 2.5 hours, and then the temperature is continued to rise to the optimal sintering temperature of the formula in normal pressure and air atmosphere, preferably 1600 to 1800°C, and then naturally cooled to room temperature after keeping warm for 2 hours.
[0030] The sintering aid can be an oxide containing metal ions, rare earth elements, etc. The electrical and mechanical properties of ceramic materials can be improved by adding metal ions, rare earth elements, etc. 2 、BaCO 3 As a sintering aid to prepare alumina (Al 2 O 3 ) composite ceramic materials, the best sintering temperatures are 1600℃, 1650℃, and 1700℃ respectively. Alumina and MgO, TiO 2 、BaCO 3 The molar ratios of MgO and TiO were 98:2 and 96:4 respectively. Undoped alumina ceramics made by the same process were used as the control group to observe their microstructure and analyze the 2 、BaCO 3 The modulation effect of doping on the microstructure of alumina ceramic materials is studied to study its influence on the temperature variation of volume resistivity, surface charge accumulation, and surface flashover voltage.
[0031] Microstructure observation method: The microstructure of ceramic samples is observed by scanning electron microscopy (SEM) to study the relationship between ceramic micromorphology and insulation performance. The sample surface needs to be cut to expose a new surface, and the surface is cleaned and gold-sprayed to avoid the influence of surface contamination and wear on the observation results, to increase the conductivity of the sample surface, and to prevent charge accumulation from affecting the image quality. By observing the microscopic image of the sample surface, the porosity, surface morphology, grain size, distribution, uniformity and number of grain boundaries of the sample can be analyzed.
[0032] The grain size of alumina without any doping ions is small, the grains are clustered, there are obvious sintering necks and pores, and the distribution is uneven, indicating that the mass transfer process is incomplete, such as Figure 1 shown.
[0033] After doping with MgO, Mg 2+ It forms a liquid phase with alumina, which leads to a reduction in the pores in the ceramic material, an increase in the grain size, and an improvement in the uniformity of the grains, e.g. Figure 2 By comparison, it can be seen that the 2% Mg 2+ The pores of alumina ceramics are significantly reduced, while the 4% Mg 2+ Porosity changes of alumina ceramics with 2% Mg doping 2+ There is not much difference between the alumina ceramics, except that the grain size is slightly reduced and the number of grain boundaries is increased.
[0034] Doped TiO 2 Later, due to Ti 4+The addition of leads to a significant increase in the ceramic grain size and a decrease in porosity, such as Figure 3 As shown. With 2% Ti doping 4+ Compared with alumina ceramics, doped with 4% Ti 4+ The grain size of alumina ceramics is larger and more disordered. 4+ This will lead to faster mass transfer during sintering. 4+ Differences in solid solubility can lead to abnormal grain growth and poor uniformity.
[0035] In doped BaCO 3 Later, due to Ba 2+ The effect of the molten-liquidity treatment significantly improves the uniformity of the grains of alumina ceramic materials, and the number of grain boundaries increases. Figure 4 Compared with 2% Ba doping 2+ Alumina ceramics doped with 4% Ba 2+ The alumina ceramic grain structure is smoother, the grain uniformity is stronger and the porosity is smaller.
[0036] The insulation properties of alumina ceramics doped with 2% of the above three different ions are as follows: Figure 5 Compared with undoped alumina ceramics, Mg-doped 2+ 、Ti 4+ and Ba 2+ Ions greatly increase the volume resistivity of alumina, especially doped Ti 4+ The volume resistivity of Mg is the highest, and 2+ with Ba 2+ It has good temperature stability. 2+ and Ba 2+ It can significantly inhibit the surface accumulation characteristics of alumina ceramics and increase the surface flashover voltage of the material, especially Ba-doped 2+ The surface charge density of alumina ceramics is significantly reduced to 0.41pC / mm 2 , the surface flashover voltage increased to 67.07kV, which is 91.73% lower than the surface charge density of undoped alumina, and the surface flashover voltage increased by 35.09%.
[0037] Combined with the above characteristics, after doping with sintering aids, Mg 2+ and Ti 4+ It promotes the sintering of alumina, thus significantly reducing the internal pores of alumina, thereby improving the temperature-dependent change characteristics of the volume resistivity of the ceramic material. 2 The total doping ratio is 2% and 4%, and the doped MgO and TiO 2 The ratios of MgO-TiO are 1:4, 2:3, 3:2, and 4:1 respectively.2 The ratio of doped aluminum oxide is 4% and MgO:TiO 2 =4:1, its grain size is larger and has excellent uniformity, resulting in lower carrier concentration, larger conduction barrier, higher volume resistivity and excellent temperature stability.
[0038] In order to further optimize the surface charge accumulation and surface flashover voltage characteristics, in MgO-TiO 2 Doped alumina is based on doping with functional ions Ba 2+ Smooth grain structure, inhibit surface charge accumulation characteristics, and increase surface flashover voltage. By doping with BaCO with a mass fraction of 1%-4%, 3 , it can be concluded that BaCO 3 When the proportion of doped aluminum oxide is 4%, the conduction barrier can be further increased, thereby increasing its volume resistivity and not changing much with temperature. At the same time, it has the best surface charge suppression effect and the highest surface flashover voltage. Therefore, the optimal formula system is MgO-TiO 2 -BaCO 3 The volume resistivity of the ternary doped alumina ceramics can reach 7.64×10 15 Ω·m, the surface charge density is only 0.32pC / mm 2 The flashover voltage is as high as 70.9kV, which achieves a synergistic improvement in the insulation performance of the solid-gas interface surface of alumina ceramic materials.
[0039] This embodiment is only a preferred specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for comprehensively controlling the surface insulation performance of a ceramic material solid-gas interface, characterized in that: A sintering agent containing metal element ions or rare earth element ions is added to the ceramic material during sintering.
2. A method for comprehensive control of the surface insulation performance of a ceramic material solid-gas interface according to claim 1, characterized in that: The sintering agent is a combination of one or more.
3. The method for comprehensive control of the surface insulation performance of a ceramic material solid-gas interface according to claim 1, characterized in that: The metal element ion in the sintering agent is Mg 2+ or Ti 4+ .
4. The method for comprehensive control of the surface insulation performance of a ceramic material solid-gas interface according to claim 1, characterized in that: The rare earth element ion is Ba 2+ .
5. The method for comprehensive control of the surface insulation performance of a ceramic material solid-gas interface according to claim 1, characterized in that: The ceramic material is simultaneously added with Mg 2+ and Ti 4+ ions, and the ratio between the two is 1:4-4:
1.
6. A method for comprehensive control of surface insulation performance of solid-gas interface of ceramic material according to claim 5, characterized in that: The ceramic material is simultaneously added with Mg 2+ and Ti 4+ and Ba 2+ ions, and Ba 2+ The doping mass fraction is 1%-4%.
7. A method for comprehensive control of the surface insulation performance of a ceramic material solid-gas interface according to claim 1, characterized in that: The mass fraction of the metal element ions or rare earth element ions added during sintering in the ceramic material is 2%-4%.
8. The method for comprehensive control of the surface insulation performance of a ceramic material solid-gas interface according to claim 1, characterized in that: Mg is added to the ceramic material during sintering. 2+ 、Ti 4+ and Ba 2+ , and the mass fraction ratio among the three is 3.2%:0.8%:4%.
9. The method for comprehensive control of the surface insulation performance of a ceramic material solid-gas interface according to claim 1, characterized in that: The sintering temperature is 1600°C to 1800°C.
10. The method for comprehensive control of the surface insulation performance of a ceramic material solid-gas interface according to claim 1, characterized in that: The ceramic material is alumina.